4(x+5)+(x-3)=40

Simple and best practice solution for 4(x+5)+(x-3)=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+5)+(x-3)=40 equation:


Simplifying
4(x + 5) + (x + -3) = 40

Reorder the terms:
4(5 + x) + (x + -3) = 40
(5 * 4 + x * 4) + (x + -3) = 40
(20 + 4x) + (x + -3) = 40

Reorder the terms:
20 + 4x + (-3 + x) = 40

Remove parenthesis around (-3 + x)
20 + 4x + -3 + x = 40

Reorder the terms:
20 + -3 + 4x + x = 40

Combine like terms: 20 + -3 = 17
17 + 4x + x = 40

Combine like terms: 4x + x = 5x
17 + 5x = 40

Solving
17 + 5x = 40

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-17' to each side of the equation.
17 + -17 + 5x = 40 + -17

Combine like terms: 17 + -17 = 0
0 + 5x = 40 + -17
5x = 40 + -17

Combine like terms: 40 + -17 = 23
5x = 23

Divide each side by '5'.
x = 4.6

Simplifying
x = 4.6

See similar equations:

| 3.7*4.8= | | -3m+16=8 | | -(1-m)=-(4m+1) | | X^4-7x^3-2x^2= | | 30z=80+22z | | c+4=-3b-ac | | 5(j+4)+j=-8 | | 10y-96+3x=360 | | 7x+3(2x+11)=111 | | -4x-20=16 | | 2(f+3)-2=8+24 | | 4x+20+2x-14=0 | | 12-4x=2(6-2x) | | 4.8*3.7= | | -(8-m)=-(5m+8) | | 119=4x+3(5x+8) | | 5y-20=40 | | 2ab*4b^3= | | 4(4x+3)-2x=5 | | 25r^2+70r+45=-3 | | 16j-27=37 | | -3(x+2)-(x-2)=x+6 | | 10y+3x=456 | | 6a=9-5a | | 2k-3(2k-3)=44 | | 18x+15y=85 | | 5(j+4)+j=8 | | -152-4x=12x+56 | | 32+0.7x=50+0.3x | | 24x-16=160 | | 115+7x=3x | | 35z+25=40z |

Equations solver categories